Application of the Judd-Ofelt theory to Pr³⁺ ions in Y₂SiO₅ crystals - Zhmurin, P.N. (Functional Materials, 2007)
The results of the Judd-Ofelt theory application to Pr³⁺ doped Y₂SiO₅ are presented. For the first time for this matrix, the Ω₂, Ω₄, Ω₆ parameters have been determined and radiative lifetimes of ³P₀ and ¹D₂ multiplet states have been calculated basing on those parameters. The lifetimes obtained allow the significant influence of the channels of nonradiative quenching for the ³P₀ state to be revealed. A more precise coincidence of calculated and observed spectroscopic characteristics can be obtained only when taking into account the influence of 4f5d electron states on 4f² electron shell properties that is not considered in the framework of the Judd-Ofelt theory.